Inovação em modelo de negócios através do uso de tecnologias da indústria 4.0 em pequenas e médias empresas - Fassini, Raquel (2021)
The use of technologies to foster innovation is one of the most used tools to promote impactful innovations. In this context, Industry 4.0 is one of the exponents in terms of technological modernization, using advanced technologies in production systems that allow greater flexibility, agility, and control of production resources. By adopting new technologies, companies improve their processes and, mainly, can modify their operations and expand the markets served, thus characterizing the Innovations in the Business Model. Aiming to deepen the discussion on the subject, this research aimed to analyze how the adoption of Industry 4.0 technologies influences innovation in the business model of small and medium enterprise. To meet this need, a multiple case study was carried out with data collection based on interviews with experts on the subject and representatives of small and medium enterprise. Secondary data were used to understand the context. Data were processed using the content analysis technique and seven categories were defined a priori from the literature and 46 categories that emerged from the data were identified. As a result, in addition to barriers and facilitators already pointed out in other studies, it was noticed that there are factors that affect the adoption of I4.0 technologies by SMEs, influencing innovation in the business model. As a theoretical contribution, it is highlighted that it was possible to deepen the knowledge about IMN in SMEs, focusing on the use of technology and its impacts. Furthermore, it contributed to the discussion about the advantages of Industry 4.0 in SMEs and how the adoption of technology can contribute to innovation in their business models. As a managerial contribution, the results can provide managers with arguments about the importance of technology adoption and serve as a reference on the need for business model innovation for the company's competitiveness. The results can also serve as a basis for formulating incentive and technological development policies aimed at SMEs, as a form of economic development and increased sectoral competitiveness.